Tinjauan Ekonomi Islam pada Implementasi Gadai Emas di Pegadaian Syariah - Sakirah Sakirah; Wahyuni Wahyuni; Andi Oddang; Sitti Nikmah Marzuki (Journal of Islamic Economics and Finance, 2025)
This study discusses the practice of gold pawn in Islamic Pawnshops from the perspective of Islamic economics, focusing on the validity of the contract and the determination of ujrah (storage fees). The gold pawn product in Islamic Pawnshops involves three contracts: qardh (loan), rahn (collateral), and ijarah (storage fees). The combination of these contracts is often debated, as it is considered a hybrid contract prohibited under certain standards, such as AAOIFI. The research findings indicate that these contracts are carried out separately and in accordance with Sharia principles, making them valid. The determination of ujrah, according to the Fatwa of DSN-MUI, should be based on storage costs, not the loan amount. However, in practice, ujrah is often calculated based on the loan value, which could lead to unfairness. The results of this study show that the gold pawn practice in Islamic Pawnshops generally complies with Sharia principles, although improvements in transparency and the determination of ujrah fees are necessary. Recommendations are provided to enhance education and refine the contract mechanism to better align with Sharia.